Promotion of Tutelary Democracy as a Social Engineering Project by a Political Intellectual Movement: A Study on Yön Journal - İlhan Bilici (Zbornik Pravnog Fakulteta Sveučilišta u Rijeci, 2023)
Although the widely-accepted definition of democracy ensures governing people for the people by the people, it has been reinterpreted by the Turkish left, and it has been noted that real democracy can only be sustained via a socialist revolution. Yön Journal has gained a critical place in reinterpreting the classical definition of democracy and pioneered the construction of a socijalist ideology blended with the principles of Kemalism and nationalism. Realizing the key role of Yön Journal in Turkey’s road to democracy, this study aimed to explore how the essence of democracy was considered within the journal and what identifying characteristics the concept of democracy had within the framework of Yön Journal. In line with this purpose, grounded theory was adopted as the research methodology, and all authored and anonymous articles in 222 issues of the journal were examined through the constant comparative method and hermeneutic approach. The results revealed that Yöncüler attributed a tutelary feature to the quintessence of democracy. Correspondingly, it was concluded that the socialist ideology adopted in Yön Journal pursued a tutelary democracy, and Yöncüler did not build tutelary ideology only on the inadequacy of the people, but also on the need for a leading cadre.